2014
DOI: 10.1371/journal.pone.0094200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fatty Acid Binding Proteins Elevates Brain Anandamide Levels and Produces Analgesia

Abstract: The endocannabinoid anandamide (AEA) is an antinociceptive lipid that is inactivated through cellular uptake and subsequent catabolism by fatty acid amide hydrolase (FAAH). Fatty acid binding proteins (FABPs) are intracellular carriers that deliver AEA and related N-acylethanolamines (NAEs) to FAAH for hydrolysis. The mammalian brain expresses three FABP subtypes: FABP3, FABP5, and FABP7. Recent work from our group has revealed that pharmacological inhibition of FABPs reduces inflammatory pain in mice. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
168
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(177 citation statements)
references
References 51 publications
(61 reference statements)
6
168
2
1
Order By: Relevance
“…In vitro experiments confirmed that these cannabinoids bind the FABPs, all with a low micromolar affinity (1.04 -3.14 M). Interestingly, these affinities are only slightly lower than those observed with SBFI26, a truxillic acid compound recently identified as a specific inhibitor of the FABPs (K i for FABP3, FABP5, and FABP7 ϭ 3.86 Ϯ 0.70, 0.93 Ϯ 0.08, and 0.38 Ϯ 0.04, respectively) (16). However, unlike SBFI26, THC and CBD showed pronounced affinity for FABP3.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In vitro experiments confirmed that these cannabinoids bind the FABPs, all with a low micromolar affinity (1.04 -3.14 M). Interestingly, these affinities are only slightly lower than those observed with SBFI26, a truxillic acid compound recently identified as a specific inhibitor of the FABPs (K i for FABP3, FABP5, and FABP7 ϭ 3.86 Ϯ 0.70, 0.93 Ϯ 0.08, and 0.38 Ϯ 0.04, respectively) (16). However, unlike SBFI26, THC and CBD showed pronounced affinity for FABP3.…”
Section: Discussionmentioning
confidence: 72%
“…8). Indeed, inhibition of FABPs was recently shown to elevate brain levels of AEA in mice (16,62). This proposed mechanism of AEA modulation in humans is highly dependent on the pharmacological concentrations of cannabinoids in the brain following consumption.…”
Section: Discussionmentioning
confidence: 99%
“…CBDak anandamidaren degradazio-entzima (FAAH) inhibi dezake in vitro (19,20) eta gizakietan dagoeneko frogatu den moduan anandamidaren kontzentrazioa garunean handitu (26). Gaitasun horrek, esaterako, CBDaren psikosiaren kontrako efektuak azaltzen dituela ikusita (26), minerako ere antzekoa gerta daitekeela iradoki genezake (27). Hala ere, CBDaren gaitasun analgesikoaren inguruko ebidentziak eskasak izanik, ez dago argi zeharkako efektu hori analgesia eragiteko nahikoa den.…”
Section: Landare-kannabinoideen Eragin Analgesikoa Eta Psikoaktibitatunclassified
“…The compound was active in the acetic acid model of visceral pain, an effect blocked by rimonabant and the peroxisome proliferator-activated receptor α (PPARα) antagonist GW6471. No overt cannabinoid-like effects upon locomotion were seen (Berger et al 2012;Kaczocha et al 2014). The effects of SB-FI-26 upon neuropathic pain were less convincing: in the chronic constriction injury (CCI) model of neuropathic pain in male Fisher 344 rats, it produced a short-term effect upon thermal hyperalgesia, but was without effect upon mechanical hyperalgesia (Kaczocha et al 2014).…”
mentioning
confidence: 99%
“…No overt cannabinoid-like effects upon locomotion were seen (Berger et al 2012;Kaczocha et al 2014). The effects of SB-FI-26 upon neuropathic pain were less convincing: in the chronic constriction injury (CCI) model of neuropathic pain in male Fisher 344 rats, it produced a short-term effect upon thermal hyperalgesia, but was without effect upon mechanical hyperalgesia (Kaczocha et al 2014). It is not known if SB-FI-26 produces the same sort of memory and learning deficits as those seen in FABP5 À/À mice (Yu et al 2014).…”
mentioning
confidence: 99%